Pinkalicious & Peterrific. Best pink present [videorecording (DVD)] - Kann, Victoria (Pinkalicious & Peterrific (Television program), 2018)
Jump into all sorts of pinkamazing adventures with Pinkalicious and her brother Peter! First, it's Daddy's birthday! Find out what happens when Pinkalicious sets out to organize the most pinkatastic gift ever. Then, see what happens when it's time to celebrate Pinkville's birthday and Mommy has made a pinkeriffic invention called The Celebrator. Also included are two other pinkcredible adventures.